Vándalos. Una aproximación a la focalización prosódica en las alocuciones presidenciales durante el estallido social de Colombia en 2021 - Muñoz-Builes, Diana Marcela (2024)
The objective of this study is to analyze the mechanism of prosodic focalization used by the ex-President Iván Duque in 23 presidential speeches issued between April 22 and May 12 on 2021, during the social outbreak in Colombia. A corpus of 87 phrases was analyzed, distributed in two phases: an analysis of prosodic focalization in phrases that contained words derived from “vandal-” and “estud-”, and an analysis of focalized phrases, although they were not necessarily derived from these lexical families. The results suggest that focalized speech is characterized by a slower rhythm, longer pauses, higher values of F0, and a broader tonal range in comparison to non-focalized speech.